Efektivitas Metode Fenton Dalam Pengolahan Limbah POME (Palm Oil Mill Effluent) - Meuthia Novenjani; Rully Masriatini; Husnah Husnah (Jurnal Inovasi Teknik Kimia, 2025)
Palm Oil Mill Effluent (POME) is a liquid waste generated from palm oil processing that contains high concentrations of organic compounds and may cause environmental pollution if not properly treated. This study aims to evaluate the effectiveness of adding Fenton reagent in reducing COD, BOD, TSS, and oil and grease levels in POME wastewater. The molar ratio variations of FeSO₄ and H₂O₂ applied were 1:20, 1:40, and 1:60, with mixing times of 20 and 30 minutes at an optimum pH of 3 and a stirrer speed of 20 rpm. The results indicate that the 1:60 ratio with a mixing time of 30 minutes achieved the greatest reduction: COD decreased from 1028 mg/L to 87.4 mg/L, BOD decreased from 512 mg/L to 178 mg/L, TSS decreased from 454 mg/L to 118 mg/L, and oil and grease decreased from 223 mg/L to 17 mg/L. All parameters met or exceeded the wastewater quality standards set by the Indonesian Ministry of Environment Regulation No. 5 of 2014. The Fenton method is proven to be effective and environmentally friendly.